STRATEGI MEMBANGUN BRAND ADVOCACY DI ERA MARKETING 4.0 - Kadek Elyani Kusumasari; I Gede Sanica (JURNAL ILMIAH EDUNOMIKA, 2022)
Conditions in the transition from traditional to digital era require a new marketing approach to assist marketers in anticipating and managing the impact of this disruptive technology. Building effective branding in the era of connectivity is by building a brand advocacy. In the past, customers went through an easy buying process, namely 4A, now the process has changed to 5A. the purpose of this research is to find out the strategy applied to build the adcocay brand in the marketing 4.0 era to consumers. This study uses descriptive qualitative and interpretive through observation, documentation, and interviews with informants. Informants in this study are active social media users and know the Gubuk Baju. the results of the research at the stage of being aware of the Gubuk Baju using social media and WOM to introduce their products.appeal stage using content marketing.at the ask stage on the social media account, the Baju Baju has provided sufficient information. If consumers want to know additional information, they can use direct messages or other platforms.at the act stage, the clothes hut provides the best service to build engagement with consumers. If the consumer is satisfied with the meal, the consumer will not hesitate to recommend it to others.